Another new exotic bark beetle in Florida: Ernoporus parvulus (Eggers, 1943) (Coleoptera: Curculionidae: Scolytinae), with additional taxonomic changes - Johnson, Andrew J. (Zootaxa, 2021)
The bark beetle, Ernoporus parvulus (Eggers, 1943) was collected from Pinellas County, Florida, USA representing the first North American record of the genus. Two species previously described from the Caribbean were examined and are synonymous: Ernoporus minutus (Bright & Torres, 2006) syn. nov. and E. exquisitus (Bright, 2019) syn. nov. This beetle is likely an overlooked exotic from Africa, known only from sea hibiscus, Talipariti tiliaceum (L.) Fryxell (Malvaceae). There is no evidence that this is a threat to commercial or ornamental Hibiscus and related species.